Asiatic Acid Prevents Oxidative Stress and Apoptosis by Inhibiting the Translocation of α-Synuclein Into Mitochondria - Ding, Hongqun; Xiong, Yuyun; Sun, Jing; Chen, Chen; Gao, Jing; Xu, Huaxi (Frontiers in Neuroscience, 2018)
The association of α-synuclein (α-syn) with mitochondria occurs through interaction with mitochondrial complex I. Importantly, dDefects of in this protein have been linked to the pathogenesis of Parkinson’s disease (PD). Overexpression of α-synuclein in cells has been suggested to cause elevations of in mitochondrial oxidant radicals and mitochondrial structural and functional abnormalities in mitochondria. Asiatic acid (AA), a triterpenoid, is an antioxidant that is used for depression treatment, our previous results showedand we have shown that pretreatment of with AA can prevent PD-like damage, but the its therapeutical effects of in PD and mechanism is unclearremain unknown. In this study, we found that 0.5-2 mg AA/100 g AA diet could significantly improves drosophila climbing ability in drosophila and extends their life-span and such —effects that might bewe attributed to its antioxidant properties. Meanwhile, AA can also protected mitochondria against oxidative stress and apoptosis in a rotenone rotenone-induced cellular model. On In an isolated mitochondrial model, AA can attenuated the decline in mitochondrial membrane potential decline that was induced by α-syn. Consequently, AA maintained the membrane integrity and ATP production. Finally, we demonstrated that AA achieved its protection protects by blocking the translocation of α-syn into mitochondria. Our results suggest that mitochondria may playare crucial role in PD and that AA is an excellent candidate for PDthe prevention and therapy of this disease.